FILOSOFI HUMA BETANG DAN SPIRITUALITAS KOMUNITAS KRISTIANI DI KALIMANTAN TENGAH: SEBUAH REFLEKSI TEOLOGIS KONTEKSTUAL - Marianus Rago Kristeno; Intansakti Pius X; Emmeria Tarihoran (JAPB: Jurnal Agama, Pendidikan dan Budaya, 2025)
The philosophy of Huma Betang serves as a moral foundation in the traditional culture of the Dayak communities in Central Kalimantan. Through inculturation, the Church internalizes the values contained in the Huma Betang philosophy by relating them to the spiritual values of communal life. This study aims to explore the points of convergence between the philosophical values of Huma Betang and Christian communal spirituality, as well as to reflect on their relevance for the life of local Catholic communities. Using a qualitative approach through a contextual reflective theological method, this research examines literature related to Dayak culture, Church documents, and the principles of inculturation. The findings indicate that the values of togetherness, equality, mutual cooperation, tolerance, and social responsibility in Huma Betang correspond to the principles of koinonia, diakonia, and martyria in the Catholic Church. These values not only function as a bridge for inculturation but also enrich pastoral practice, catechesis, and the faith experience of the community. The implications of this study affirm that integrating local cultural values into the life of the Church can deepen the faith identity of the community, strengthen the spirit of synodality, and help build the Church as an inclusive and solidaristic common home. Thus, Huma Betang can serve as a theological and pastoral inspiration for developing Christian communal spirituality in Central Kalimantan.